2016
DOI: 10.1186/s12905-016-0354-y
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual pattern among adolescent girls of Pokhara Valley: a cross sectional study

Abstract: BackgroundMenstruation is a normal physiological process occurring every month throughout the reproductive age of the females. However, significant variation in menstrual pattern is observed among adolescents. The objective of this study was to determine menstrual pattern among adolescent girls of Pokhara Valley.MethodA cross sectional study was conducted in seven schools of Pokhara Valley. A total of 260 adolescent girls were included in the study. Girls were requested to complete questionnaire containing 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 12 publications
4
48
3
3
Order By: Relevance
“…In the present study, the mean age at menarche was 12.96 ± 1.09 years old, similar to that in the literature . Onset of menstruation before the age of 12 years, however, was found to increase the risk of menstruation‐related headache.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, the mean age at menarche was 12.96 ± 1.09 years old, similar to that in the literature . Onset of menstruation before the age of 12 years, however, was found to increase the risk of menstruation‐related headache.…”
Section: Discussionsupporting
confidence: 89%
“…16 And Arjona et al 17 noted that 10% of women treated at a tertiary center between 1998 and 2003, reported that their headache was related to menstruation. In 2006, Sharma et al 18 found that the severity of headache increases during menstruation in 9% of women with cluster headache.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al., 2014). Lifestyle management by regulating considerable physical activity, reducing fast-food consumption, healthy eating habits, keeping the ideal BMI are few ways to improve reproductive health, particularly in maintaining regular menstrual cycle (Jena, Panda, Mishra, and Narahari, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It may vary with races, size of the family and environmental factors. 2,10,11 Reports have shown that, age at menarche varies with passage of time, occurring earlier than it did (earlier in new generation than old generation). 2,9,10,12 Menarche tends to occur earlier in higher social class and in urban surroundings due to food habits (junk food) and use of internet causing early maturity.…”
Section: Introductionmentioning
confidence: 97%